2021
DOI: 10.3390/genes12091377
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Immunity-Related Genes and Their Effects on Immunophenotypes in Different Pig Breeds

Abstract: Enhancing resistance and tolerance to pathogens remains an important selection objective in the production of livestock animals. Single nucleotide polymorphisms (SNPs) vary gene expression at the transcriptional level, influencing an individual’s immune regulation and susceptibility to diseases. In this study, we investigated the distribution of SNP sites in immune-related genes and their correlations with cell surface markers of immune cells within purebred (Taiwan black, Duroc, Landrace and Yorkshire) and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Future studies are therefore required to formally demonstrate the involvement of RNA sensors in ASFV sensing and to characterize at which stage of the ASFV replication cycle this detection takes place. Interestingly, multiple single nucleotide polymorphisms (SNPs) in TLRs have been observed in wild boars ( Bergman et al, 2010 ) and in some specific breeds of domestic pigs ( Palermo et al, 2009 ; Chen et al, 2021 ), and hence it would therefore be interesting to assess their effect on ASFV innate immune sensing.…”
Section: Recognition Of African Swine Fever Virus By Other Sensorsmentioning
confidence: 99%
“…Future studies are therefore required to formally demonstrate the involvement of RNA sensors in ASFV sensing and to characterize at which stage of the ASFV replication cycle this detection takes place. Interestingly, multiple single nucleotide polymorphisms (SNPs) in TLRs have been observed in wild boars ( Bergman et al, 2010 ) and in some specific breeds of domestic pigs ( Palermo et al, 2009 ; Chen et al, 2021 ), and hence it would therefore be interesting to assess their effect on ASFV innate immune sensing.…”
Section: Recognition Of African Swine Fever Virus By Other Sensorsmentioning
confidence: 99%
“…TLRs recognize conserved patterns of pathogens by binding residues, known as antigens, from pathogens that enter the body (Singh et al, 2003). Pathogen recognition by TLRs is necessary for the proper activation and direction of the adaptive immune response (Chen et al, 2021; Clark & Kupper, 2005; Kawasaki & Kawai, 2014; Pasare & Medzhitov, 2005; Xia et al, 2021). Studies have found that TLR gene diversity tends to be low in small, highly threatened populations compared to large populations of species of least concern (Alcaide & Edwards, 2011; Dalton et al, 2016; Knafler et al, 2017; Morrison et al, 2020).…”
Section: Introductionmentioning
confidence: 99%